Предмет: Алгебра,
автор: Аноним
Розв'яжіть нерівність: 3(х – 5) + 2 > 2(х – 1) + 3(х + 2);
Ответы
Автор ответа:
0
Відповідь:
3(х-5)+2>2(х-1)+3(х+2)=
3х-15+2>2х-2+3х+6=
-15+2>2х-2+6=
-13>2х+4=
-2х>4+13
-2х>17 | :(-2)
х < -17/2
або
3(х-5)+2>2(х-1)+3(х+2)=
3х-15+2>2х-2+3х+6=
-15+2>2х-2+6=
-13>2х+4=
-2х>4+13
-2х>17 | :(-2)
х < -17/2
Пояснення:
Автор ответа:
0
Объяснение:
3x-15+2>2x-2+3x+6
3x-2x-3x>-2+6+15-2
-2x>17
x<-8,5
x=(-∞;-8,5)
Похожие вопросы
Предмет: Математика,
автор: eleonoraoleshko
Предмет: Другие предметы,
автор: sabraevasabina8
Предмет: Математика,
автор: ritkissq
Предмет: Математика,
автор: klimavadasa